Obesity and hospital outcomes following traumatic injury: Associations in 9 years of patient data from a single metropolitan area. Issue 2 (18th January 2019) - Rock, Kathryn; Hayward, Richard D.; Edhayan, Elango
Abstract : Traumatic injury is a leading cause of death and disability worldwide. Obesity may put trauma patients at risk for complications leading to negative clinical outcomes. Data on all hospital admissions due to traumatic injury in the Detroit metropolitan area between 2006 and 2014 were obtained from the Michigan State Inpatient Database. Generalized linear modelling was used to compare patients with and without obesity on three outcomes: mortality, length of hospital stay and total charges for care. Adjusting for demographics, patients with obesity had 26% longer hospitalization. Adjusting for demographics and length of stay, charges were 8% higher. Obesity was unrelated to mortality. Obesity had greater impact on length of stay among younger adults; its relationship with charges emerged only among older adults. Obesity has significant clinical implications for trauma care. Demands for trauma care resources, and the charges associated with providing care, are likely to increase as obesity rates rise.